14‐day reverse hybrid therapy vs 7‐day concomitant therapy in the first‐line treatment of Helicobacter pylori infection. Issue 1 (3rd December 2020) - Chang, Shiuh‐Nan; Shih, Yung‐Hsiung; Lee, Wen‐Ching; Kuo, Ming‐Te; Tsay, Feng‐Woei; Kuo, Li‐Fu; Huang, Wen‐Wei; Shie, Chang‐Bih
Abstract: Increasing antibiotics resistance poses a great challenge for the treatment of Helicobacter pylori ( H. pylori ) infection. The reported eradication rates of 7‐day standard triple therapy have fallen below 80% in most countries due to increasing clarithromycin resistance. Both 14‐day reverse hybrid therapy and 7‐day concomitant therapy have been reported to yield high eradication rates for the treatment of H. pylori infection. However, whether 14‐day reverse hybrid therapy can achieve a higher eradication rate than 7‐day concomitant therapy remains unanswered. The aim of this study is to compare the efficacies of 14‐day reverse hybrid and 7‐day concomitant therapies for the first‐line treatment of H. pylori infection in a primary care setting. From May 2016 to December 2019, 322 H. pylori ‐infected patients receiving either 14‐day reverse hybrid therapy (a proton pump inhibitor [PPI] plus amoxicillin 1 g b.d. for 14 days, and clarithromycin 500 mg plus metronidazole 500 mg b.d. for the initial 7 days, n = 142) or 7‐day concomitant therapy (PPI plus amoxicillin 1 g, clarithromycin 500 mg, and metronidazole 500 mg b.d. for 7 days, n = 180) in our clinic were included in the retrospective study. All the patients underwent a follow‐up endoscopy with a rapid urease test or a urea breath test at least 4 weeks after completion of anti‐ H. pylori therapy and at least 2 weeks after discontinuation of PPI. Intention‐to‐treat analysis demonstrated a significantly higher eradication rate for the 14‐day reverse hybrid group than for the 7‐day concomitant group (95.8% vs 88.9%, P  = .024). Per‐protocol analysis also yielded similar results (97.8% vs 90.3%, P  = .009). Both groups had similar frequencies of adverse events (14.1% vs 13.9%, P  = .990) and drug compliance (95.8% vs 97.2%, P  = .478). Conclusions: Fourteen‐day reverse hybrid therapy achieves a higher eradication rate than 7‐day concomitant therapy in the first‐line treatment of H. pylori infection.